2012
DOI: 10.1037/a0025424
|View full text |Cite
|
Sign up to set email alerts
|

Substance use in lesbian, gay, and bisexual populations: An update on empirical research and implications for treatment.

Abstract: Historically, substance use problems were thought to be more prevalent in lesbian, gay, and bisexual (LGB) populations, and correcting skewed perceptions about substance abuse among LGB individuals is critically important. This review provides an update on empirical evidence on LGB substance use patterns and treatment outcome, with specific focus on clinical implications of findings. Compared to earlier studies, the recent research included in this review has used more sophisticated methodologies, more represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
274
3
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(298 citation statements)
references
References 64 publications
15
274
3
6
Order By: Relevance
“…For example, there is a positive relationship between neighborhood alcohol outlet density and social norms regarding alcohol use, as well as rates of alcohol consumption (Scribner et al, 2000). In this regard, the social organization of a visible gay and lesbian community, traditionally centered on "gay bars" and social outlets, may encourage the use of alcohol and illicit drugs (Green and Feinstein, 2011;Simon Rosser et al, 2008). The effect may be to create a climate of tolerant injunctive social norms surrounding substance use in which illicit drugs are, in turn, more readily available.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a positive relationship between neighborhood alcohol outlet density and social norms regarding alcohol use, as well as rates of alcohol consumption (Scribner et al, 2000). In this regard, the social organization of a visible gay and lesbian community, traditionally centered on "gay bars" and social outlets, may encourage the use of alcohol and illicit drugs (Green and Feinstein, 2011;Simon Rosser et al, 2008). The effect may be to create a climate of tolerant injunctive social norms surrounding substance use in which illicit drugs are, in turn, more readily available.…”
mentioning
confidence: 99%
“…However, the same study also found contradictory evidence with regard to men. Specifi cally, rates of heavy drinking among men did not vary by sexual orientation across settings, even though gay men spent more time in bars than bisexual and heterosexual men did.Some researchers (Cochran, 2001;Green and Feinstein, 2011;McKirnan and Peterson, 1989) have speculated that tolerant norms regarding drug use are endemic among sexual orientation minorities, particularly among those living in areas of higher gay density. In one study of more than 700 gay men living in New York City, men with more "gay-centric" networks had higher rates of substance use (Carpiano et al, 2011).…”
mentioning
confidence: 99%
“…In addition, studies that test alternative theories that explain substance use among LGB individuals simultaneously to understand their interconnection and/or independent contributions are sorely needed. For example, understanding the interplay of minority stress with potentially learned or reinforced social behaviors will be crucial for initiating the most effective interventions, whether at a macro or a micro level (Green & Feinstein, 2012).…”
Section: Future Researchmentioning
confidence: 99%
“…Empirical evidence mostly supports the negative effects of internalized heterosexism on poorer mental health outcomes, such as alcohol use and psychiatric disorders (Green & Feinstein, 2012;Hatzenbuehler, 2009). Meta-analyses show that internalized heterosexism is associated with internalizing mental health problems, such as depression, and risky sexual behaviors among sexual minority men (Newcomb & Mustanski, 2010.…”
mentioning
confidence: 99%
See 1 more Smart Citation